Evaluation Of Training Deficiencies In Vocational Guidance By The Educational Counselor - Assist. Prof. Ashraf Saleh Jasim, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to evaluate training deficiencies in vocational guidance by the educational counselor, to identify the extent of the capacity of the field of professional theories, occupational classification, standards, training needs, and training requirements to develop training deficiencies in career guidance by educational counselors. Also, identifying whether there are statistically significant differences at the level of (0.05) among the individuals of the basic research sample in the general average for each of the ability of the field (professional theories, professions classification, standards, training needs, training requirements) to develop training needs in Vocational guidance according to the gender variable (males, females). After completing the preparation of the research tool and ensuring its validity and stability, the basic application was carried out on the basic research sample of 103 male and female mentors with the aim of evaluating training deficiencies in career guidance by the educational counselor, and identifying the significance of the differences between them in terms of gender in this field.